Dinamika dan Pergeseran Sektor Basis Perekonomian Kabupaten Ciamis terhadap Jawa Barat - Greshinta, Naora Yolla; Fitria, Ananda Marda; Taufiqqurrachman, Fahrizal (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The analysis of base sectors is a crucial component of regional economic development planning to promote sustainable growth. This study aims to identify base sectors and analyze the dynamics and structural shifts of the economy of Ciamis Regency relative to West Java Province based on sectoral Gross Regional Domestic Product (GRDP) data at constant prices. The analytical methods employed are the Location Quotient (LQ) to determine base and non-base sectors, and the Dynamic Location Quotient (DLQ) to examine sectoral growth trends over time. The results indicate that several sectors in Ciamis Regency have LQ values greater than one, reflecting comparative advantages over West Java Province. Furthermore, the DLQ analysis reveals that some sectors classified as non-base sectors structurally exhibit higher growth rates compared to the reference region. This condition suggests the existence of economic dynamics and potential shifts in the regional base sectors. Therefore, the combined use of LQ and DLQ provides a more comprehensive understanding of the current condition and future prospects of regional economic sectors. The findings of this study are expected to serve as a reference for formulating more targeted and effective economic development policies in Ciamis Regency.